Two-scale Monte Carlo ray tracing for canopy-leaf vector radiative transfer coupling. (March 2020) - Kallel, Abdelaziz
Highlights: Vector radiative transfer to model leaf-canopy polarized reectance is proposed. Decomposing incident light into a basis of polarization allows to derive the Stokes phase function at leaf level. Discretizing wavelength domain, incident and exiting angles allows to create a database of Stokes phase function. Monte Carlo weighted sampling allows to predict the ray tracing from one wavelength to another on leaf and canopy levels. Polarization and 3-D structure of leaves are not negligible. Abstract: Canopy reflectance simulation was widely developed using Monte Carlo (MC) ray tracing. Nevertheless, the proposed models assume leaf as Bi-Lambertian medium. Based on the recently developed leaf MC ray tracing code, this study proposes to couple MC ray tracing simulations on leaf and canopy levels. Firstly, at the first level, the bidirectional scattering distribution function (BSDF) is computed for unpolarized incoming rays as well as some common states of polarization producing together a polarization decomposition basis, allowing to derive the Stokes phase function. Moreover, discretizing both incident and scattering angles over the sphere allows to produce a database of all possible Stokes phase functions. Secondly, at the canopy level, the reflectance is simulated using ray tracing technique, when ray is intercepted, the scattering is done considering the appropriate Stokes phase function in the leaf database. Simulation of multiple wavelengths is accelerated based on a new MC weighted sampling technique permitting to consider the same tracing for all the wavelengths together. Simulation results show the relevance of such modeling compared to traditional models. Indeed, from one side the canopy bidirectional reflectance depends on the leaf BSDF thus if leaves are assumed Bi-Lambertian surfaces leads to inaccurate results, and from the other side, the reflectance is sensitive to polarization and neglecting it affects the results mainly when the incident light is polarized. Comparison with actual polarized reflectance measurements presented in literature shows good agreement with same trends and variation ranges. Quantitative validation of our canopy level model is done using the ROMC web-tool. Reflectance RMSE between our simulations and the ROMC reference is lower than 0.02.